Segmented asset markets and optimal exchange rate regimes - Lahiri, Amartya; Singh, Rajesh Kumar 1961-; Végh, Carlos A. 1958- (Working paper series / National Bureau of Economic Research, 2007)
This paper revisits the issue of the optimal exchange rate regime in a flexible price environment. The key innovation is that we analyze this question in the context of environments where only a fraction of agents participate in asset market transactions (i.e., asset markets are segmented). Under this friction, alternative exchange rate regimes have different implications for real allocations in the economy. In particular -- and contrary to standard results under sticky prices -- we show that flexible exchange rates are optimal under monetary shocks and fixed exchange rates are optimal under real shocks.